Treatment of Acquired von Willebrand Syndrome and Prevention of Bleeding Postautologous Stem Cell Transplant during Severe Pancytopenia with IVIG. (2nd April 2015) - Zoghi, Behyar; Shaughnessy, Paul; Lyons, Roger M.; Helmer, Richard; Bachier, Carlos; LeMaistre, C. Frederick
Abstract : The use of high dose chemotherapy followed by autologous hematopoietic stem cell transplantation for remission consolidation after initial induction represents standard of care for patients with multiple myeloma. Patients with myeloma and Acquired von Willebrand Syndrome (AVWS) undergoing autologous stem cell transplant (ASCT) are at significant risk of bleeding due to the profound thrombocytopenia, low Factor VIII levels, fever, and toxicities associated with the preparative regimen. We report a patient with AVWS associated with multiple myeloma who underwent autologous stem cell transplants as consolidation after initial induction and again at relapse. He was successfully treated with high dose intravenous immunoglobulin (IVIG) prior to each transplant with rapid resolution of AVWS.